KARAKTERISTIK PENDERITA HIPERTENSI DENGAN KOMPLIKASI YANG DIRAWAT INAP DI RS SANTA ELISABETH MEDAN TAHUN 2011-2015 - Fredrick Alexander Marpaung; Hiswani .; Sri Novita Lubis (Gizi, Kesehatan Reproduksi dan Epidemiologi, 2017)
Hypertension is the number one cause of illness in developed countries, the number two cause of illness in developing countries, the number one cause for the risk of stroke and heart failure, and the number two cause for the risk of heart attack. In Indonesia, one of three adults were people with hypertension. Prevalence of Hypertension in Indonesia obtained through measurement at age ≥18 years old was 25.8%. This is a descriptive study with case series design, and continued with the analysis of statistic chi square test, fisher test, dan kolmorgorov-smirnov test. This study aims to determine the characteristics of patients with Hypertension with complications who were hospitalized at the Santa Elisabeth Hospital Medan in 2011-2015. Population and sample were same (total sampling) which were 101 inpatients with hypertension with complications. Data is secondary data taken from the patient’s medical record. The result showed the proportion of patients the most at age ≥40 years (96.0%), women (57.4%), Batak (82.2%), Protestants (54.5%), did not work (41.5 %), married (95.0%), in Medan (74.3%), headache (65.3%), hypertension stage 2 (53.5%), diabetes mellitus (34.7%), average of treatment duration was 5.45 days, out as outpatient (84.1%). There was no significant difference between the proportions of age by complications of hypertension (p = 0.101), there was no significant difference between the proportion of sexes by complications of hypertension (p = 0.652), there was no significant difference between the proportion of work categories by complications of hypertension (p = 0.756), there was no significant difference between the proportion of Hypertension degrees by complications of hypertension (p = 0.485), the distribution for average of treatment duration by category of complications with acute complications were 4.18 days and chronic complications were 6.06 days , there was no significant differences between the proportion of discharged status by complications of hypertension (p = 0.164). The hospital authorities should give a promotions or information that is important for everyone's to check their blood pressure routinely in order to anticipate and prevention of hypertension disease. Suggest the patients with hypertension to organize a good diet like the DASH dietary and recommend them to havea healthy lifestyle like increasing physical activity by exercising regularly. The medical officer who in charge kindly give more attention to fill the columns data of patient Hypertension with complications status especially in how the patients go out from the hospital. Keywords: Hypertension, Characteristic, Hospitalized, Santa Elisabeth Hospital Medan